Hedge funds in emerging markets - De Brouwer, Gordon J (Cambridge Univ. Pr, 2010)
Hedge funds are among the most innovative and controversial of financial market institutions. Largely exempt from regulation and shrouded in secrecy, they are credited as having improved efficiency and add liquidity to financial markets, but also having severely destabilised markets following the Asian financial crisis and the near collapse of long-term capital management. De Brouwer presents a nuanced and balanced account to what is becoming an increasingly politicised and hysterical discussion of the subject. Part I explains the workings of hedge funds. Part II focuses on the activities of macro hedge funds and proprietary trading desks in East Asia in 1997 and 1998, with case study material from Hong Kong, Indonesia, Malaysia, Singapore, Australia and New Zealand. Part III of the book looks at the future of hedge funds, their role for institutional investors, and policy proposals to limit their destabilising effects.